THE TALENT WAR IN A REMOTE-FIRST WORLD: HR STRATEGIES FOR ATTRACTION AND RETENTION - Niken Wulandari; Ramon Zamora; Dhenny Asmarazisa (RADJA PUBLIKA, 2026)
The rapid shift to remote and hybrid work models has fundamentally transformed the global talent landscape, intensifying competition for skilled professionals beyond geographical boundaries. This article examines the strategic human resources responses necessary to win the talent war in this remote-first era. The objective is to identify and analyze effective HR strategies for attracting and retaining top talent in a distributed work environment. Utilizing a mixed-methodology approach, the research combines a comprehensive review of recent academic and industry literature with a qualitative analysis of case studies from leading remote-first organizations. The findings reveal that success hinges on moving beyond replicating office-centric practices digitally. Key strategies include building a compelling employer brand anchored in flexibility and autonomy, redesigning total rewards packages to prioritize flexibility and holistic well-being, implementing intentional practices to foster connection and combat isolation, and leveraging technology for equitable performance management. The discussion emphasizes that talent attraction and retention are now integrated outcomes of a holistic employee experience designed for a distributed workforce. The conclusion asserts that organizations must view remote work not as a temporary adjustment but as a core strategic component, requiring a fundamental re-evaluation of HR policies and leadership approaches to build a sustainable competitive advantage in the new talent economy.